Determination of Atomic Number Exponent for Elemental Absorber at Am– 241 Energy in X–Ray Attenuation Experiments - Najim, Laith Ahmed; Shamoon, Sabeeh Karyakos; Atalah, Shiama Talal (Al-Nahrain Journal of Science, 2012)
In X-ray absorption experiment, the dependence of the photoelectric absorption cross-sectionvaried with atomic number Z. In this paper, the dependence on Z of the cross – section orcoefficient of photoelectric absorption is first evaluated from published data for (20) elementsranging from Al–Sn, and then the cross–section for Fe is obtained experimentally by measuring theX-ray intensity with and without the Fe absorber and compared with the theoretical value, thevariation of the photoelectric absorption coefficient (μ/ρm) showed less dependence on Z for the twotested of Z regions. This is because of the inclusion of mass density (ρm) of the absorber in thecoefficient. The values of m obtained in the present work increases linearly with energy for bothranges of elements.